Analysis of different friction factor correlations on the frictional pressure drop of two-phase flow ammonia-cooled minichannel - Shaari, Muhammad Syafiq (2015)
Friction factor is one of the major parameters that affect the frictional pressure drop in a mini channel of a compact heat exchanger. There have been many studies on the correlations for the friction factor, both in implicit and explicit forms. Differences between the predicted and experimental pressure drop have been reported and these could possibly be due to the different correlations used.This paper reports the effects of using five different friction factor correlations, both in implicit and explicit forms,on the frictional pressure drop of an ammonia-cooled minichannel under optimized conditions. For turbulent flow in a smooth channel, optimization is completed for 0.9-mm and 3-mm channels with genetic algorithm. Results show that different friction factor correlations produced different values of the frictional pressure drop even under optimized conditions.All five correlations produced evenly distributed optimal solutions for the simultaneous optimization of the frictional pressure drop and heat transfer coefficients. Comparison of R22 and ammonia refrigerants showed that the latter produced a higher heat transfer coefficient at the cost of a higher frictional pressure drop under optimized conditions.